Room for Two: The Synaptophysin/Synaptobrevin Complex - White, Dustin N.; Stowell, Michael H. B. (Frontiers in Synaptic Neuroscience, 2021)
Synaptic vesicle release is regulated by upwards of 30 proteins at the fusion complex alone, but disruptions in any one of these components can have devastating consequences for neuronal communication. Aberrant molecular responses to calcium signaling at the pre-synaptic terminal dramatically affect vesicle trafficking, docking, fusion, and release. At the organismal level, this is reflected in disorders such as epilepsy, depression, and neurodegeneration. Among the myriad pre-synaptic, perhaps the most functionally mysterious is synaptophysin (SYP). On its own, this vesicular transmembrane protein has been proposed to function as a calcium sensor, a cholesterol-binding protein, and to form ion channels across the phospholipid bilayer. The downstream effects of these functions are largely unknown. The physiological relevance of SYP is readily apparent in its interaction with synaptobrevin (VAMP2), an integral element of the neuronal SNARE complex. SNAREs, soluble NSF attachment protein receptors, comprise a family of proteins essential for vesicle fusion. The complex formed by SYP and VAMP2 is thought to be involved in both trafficking to the pre-synaptic membrane as well as regulation of SNARE complex formation. Thus, the SYP/VAMP2 complex appears vital to the form and function of neuronal exocytotic machinery.